Emergence of Urban Tourism from Tourism Perspective- The Past, Present and Future-A Critical Evaluation (International Journal of Food and Nutritional Sciences, 2022)
The concept of urban tourism has attained significance all around the world from the past few years. Before that, such a scenario didn’t exist anywhere in the biosphere. While other forms of tourism saw significant growth in the 1960s and 1970s, particularly